1986
DOI: 10.1128/mcb.6.4.1135
|View full text |Cite
|
Sign up to set email alerts
|

Primary DNA sequence determines sites of maintenance and de novo methylation by mammalian DNA methyltransferases.

Abstract: Analysis of the enzymatic methylation of oligodeoxynucleotides containing multiple C-G groups showed that hemimethylated sites in duplex oligomers are not significantly methylated by human or murine DNA methyltransferase unless those sites are capable of being methylated de novo in the single-or double-stranded oligomers. Thus, the primary sequence of the target strand, rather than the methylation pattern of the complementary strand, determines maintenance methylation. This suggests that de novo and maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…The partial methylation that we see is not correlated with protein footprints and is seen only at some GCG or CGC trinucleotides; thus, there may be a bias of DNA methyhransferase against certain DNA sequences. Mammalian DNA methyhransferase does show a preference for certain CpGs in vitro (Bolden et al 1986;Smith et al 1989). The undermethylated GCG trinucleotides that we find are surrounded by several G/C base pairs and, thus, are very G + C-rich sites.…”
Section: Methylation Of Cpg Islandsmentioning
confidence: 78%
“…The partial methylation that we see is not correlated with protein footprints and is seen only at some GCG or CGC trinucleotides; thus, there may be a bias of DNA methyhransferase against certain DNA sequences. Mammalian DNA methyhransferase does show a preference for certain CpGs in vitro (Bolden et al 1986;Smith et al 1989). The undermethylated GCG trinucleotides that we find are surrounded by several G/C base pairs and, thus, are very G + C-rich sites.…”
Section: Methylation Of Cpg Islandsmentioning
confidence: 78%
“…In addition, it has been proposed that viral enhancer sequences may have the intrinsic ability to interact with cellular proteins, thereby perturbing the interaction of the methylase with DNA (Jfihner & Jaenisch, 1985b;Bird, 1986). It is therefore possible that in Rat-9G cells the IE upstream region interacts with proteins that prevent methylation, or that resistance is determined by the primary DNA sequence (Bolden et al, 1985(Bolden et al, , 1986Zacharias et al, 1984;Vardimon & Rich, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy still exists as to the existence of two distinct enzymes, since the de novo and maintenance methyltransferase activities do co-purify (26,44,46). Initially, the sequence specificities of the two enzymes were thought to be different (35,47), but recently Bolden et al suggested that both methyltransferase reactions are catalyzed by the same enzyme, as the maintenance and de novo methyltransferases share the same substrate specificities (48). It has also been postulated that DNA methyltransferase associated with the nuclear matrix is predominantly responsible for the maintenance of inheritable methylation patterns (49,50), but does also possess some de novo methylation activity (49).…”
Section: Dna Methylation Patternsmentioning
confidence: 99%